Increasing the Growth and Quality of Red Chili with Growth Hormone from Endophytic Bacteria - Rafika Yuniawati; Siti Fatimah; Reni Indrayanti; Ifa Manzila; Tri Puji Priyatno; Dwi Ningsih Susilowati (Jurnal AgroBiogen, 2019)
Red chili is a very important horticultural commodity in Indonesia having low productivity and quality. Cultivation method needs to be improved including the use of exogenous growth hormones. The purpose of this study was to determine (1) the optimum concentration of IAA and GA growing hormones from isolate B6.2 in stimulating plant growth and improving the quality of large red chili fruit; (2) molecular identity of the B6.2 bacterial isolate. The growth hormone content of B6.2 isolates using HPLC obtained 0.49 ppm IAA and 64.53 ppm GA. The growth hormone potential test on the growth and quality of chili was carried out with a concentration of 1, 3, 5 ml/l, while water and synthetic hormones was used as negative and positive control, respectively. The experimental design used was a Complete Random Design with the foliar spray application to the plant canopy three times during the growth period. The results showed the best concentration in increasing plant height, fruit weight, shooth wet, and dry weight compared to controls at the age of 76 days after planting (dap) was a concentration of 5 ml/l, with the values of 71.7±0.9 cm , 94.7±0.3 g, 11.5±0.43 g, and 1.4±0.09 g, respectively. The molecular identification showed that B6.2 isolate was classified as Bacillus vallismortis with 100% homology. The growth hormone from isolate B6.2 has the potential to increase growth and production of red chili plants.